2003
DOI: 10.1086/375777
|View full text |Cite
|
Sign up to set email alerts
|

Tracing the Large‐Scale Structure in theChandraDeep Field South

Abstract: We report the discovery of large-scale structures of X-ray sources in the 1 Ms observation of the Chandra Deep Field South. Two main structures appear as narrow (Dzd0:02) spikes in the source redshift distribution at z ¼ 0:67 and 0.73, respectively. Their angular distribution spans a region at least $17 0 wide, corresponding to a physical size of 7:3 h À1 70 Mpc at a redshift of z $ 0:7 ( m ¼ 0:3, Ã ¼ 0:7). These spikes are populated by 19 sources each, which are mainly identified as active galactic nuclei (AG… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

51
223
1
2

Year Published

2004
2004
2017
2017

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 165 publications
(277 citation statements)
references
References 27 publications
51
223
1
2
Order By: Relevance
“…Two main clumps appear about redshifts 0.70, 1.00. A comparison with the distribution of spectroscopic redshifts of the CDFS (see Gilli et al 2003, Fig. 1) clearly indicates the reality of the two clumps, although the two peaks at z = 0.67 and z = 0.73 found by Gilli et al (2003) in the distribution of spectroscopic redshifts are barely resolved in our photometric redshift distribution.…”
Section: Galaxy Clusters In the Chandra Deep Field Southmentioning
confidence: 50%
See 3 more Smart Citations
“…Two main clumps appear about redshifts 0.70, 1.00. A comparison with the distribution of spectroscopic redshifts of the CDFS (see Gilli et al 2003, Fig. 1) clearly indicates the reality of the two clumps, although the two peaks at z = 0.67 and z = 0.73 found by Gilli et al (2003) in the distribution of spectroscopic redshifts are barely resolved in our photometric redshift distribution.…”
Section: Galaxy Clusters In the Chandra Deep Field Southmentioning
confidence: 50%
“…The first structure, at z = 0.70 is approximately centred on the cD galaxy, whose position, in turn, corresponds to the centre of the extended X-ray source CDFS566 (Giacconi et al 2002). As noted above, we cannot resolve, in redshift space, the walllike structure at z = 0.67 described by Gilli et al (2003) which then contaminates the structure at z = 0.70. In spite of that we find a relatively concentrated structure with full width at half maximum of about 0.12 Mpc.…”
Section: Galaxy Clusters In the Chandra Deep Field Southmentioning
confidence: 90%
See 2 more Smart Citations
“…Our first application to the K20 survey (Cimatti et al 2002) detected two clusters at z ∼ 0.7 and z ∼ 1 ), previously identified through spectroscopy (Gilli et al 2003;Adami et al 2005). We then applied the algorithm to the much larger GOODS-South field, and in Castellano et al (2007), elsewhere C07, we reported our initial results, i.e.…”
Section: Introductionmentioning
confidence: 99%